2017
DOI: 10.1038/s41467-017-01983-6
|View full text |Cite
|
Sign up to set email alerts
|

Scaling relationships and theory for vibrational frequencies of adsorbates on transition metal surfaces

Abstract: Adsorbate vibrational excitations are an important fingerprint of molecule/surface interactions, affecting temperature contributions to the free energy and impacting reaction rate and equilibrium constants. Furthermore, vibrational spectra aid in identifying species and adsorption sites present in experimental studies. Despite their importance, knowledge of how adsorbate frequencies scale across materials is lacking. Here, by combining previously reported experimental data and our own density-functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 73 publications
1
52
0
Order By: Relevance
“…The dataset is located in Supplementary Tables 1 and 2. In addition to describing chemisorbed CO frequencies well, the relative intensities for chemisorbed CO spectra can be computed reliably from DFT despite significant errors in DFTcalculated CO adsorption energies 28,30,31 . CO frequencies do not correlate with adsorption energy as the governing physics for each is different (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dataset is located in Supplementary Tables 1 and 2. In addition to describing chemisorbed CO frequencies well, the relative intensities for chemisorbed CO spectra can be computed reliably from DFT despite significant errors in DFTcalculated CO adsorption energies 28,30,31 . CO frequencies do not correlate with adsorption energy as the governing physics for each is different (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CO is extensively used as a probe molecule for IR studies because of its well-defined peaks. It is also ideal for computations because its frequencies can be computed accurately 28 , its distinctive C-O stretch frequency depends on both site type 28 and coordination 50 , and its vibrational modes are driven by interaction with the metal surface 31 . We extend the model using NO as a probe molecule in the SI because NO binds in a similar manner to CO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we calculated the pyrrole adsorption energies [Δ E ads (C 4 H 5 N)] at active (μ‐O) sites for all the models and the corresponding redshifts of NH stretching vibrations [∆ v NH (C 4 H 5 N)], and explored the dependency of the Δ E int ≠ on these parameters (Table , Figure d,e). Lansford et al demonstrated that the following empirical relation exists for the frequency dependency on adsorption energyv2=αΔEads+βwhere α and β are constants. Therefore, the [∆ v NH (C 4 H 5 N)] 2 was used as a linear function of Δ E int ≠ .…”
Section: Resultsmentioning
confidence: 99%
“…The development of scaling relations represents an important advance, which link the activation barriers with the adsorption properties of chemical species across different catalyst surfaces . This allows the description of the catalytic activity in terms of structural properties such as adsorption energies or vibrational frequencies of reaction intermediates or guest probe molecules . A better understanding of the property–reactivity relationships enables an accelerated predication of catalyst performance and an improved efficiency of catalyst screening and design.…”
Section: Introductionmentioning
confidence: 99%